The core promoter controls basal and inducible expression of duck retinoic acid inducible gene-I (RIG-I). (November 2018) - Xiao, Yanna; Reeves, Matthew B.; Caulfield, Adam F.; Evseev, Danyel; Magor, Katharine E.
Highlights: Duck RIG-I promoter controls basal and inducible expression in duck and chicken cells. Luciferase assays of promoter deletions reveal a 250 bp core promoter. Deletion and mutation analysis identify cis- elements controlling expression. IRF-7 activates the promoter through an ISRE downstream of MAVS signaling. Abstract: Retinoic acid inducible gene-I (RIG-I) is a cytoplasmic RNA sensor for detecting a variety of RNA viruses including influenza A viruses. Detection ultimately produces Type I interferon (IFN), which stimulates expression of interferon stimulated genes (ISGs), including RIG-I itself in a positive feedback loop. The structure and function of RIG-I is conserved across phylogeny, despite significant protein sequence divergence, however, the promoter sequences do not show the expected phylogenetic relationships and it is not known whether they are similarly regulated. We previously cloned duck RIG-I and showed it is highly induced during influenza A infection consistent with induction by the interferon produced. Here, we identified the Pekin duck RIG-I promoter and constructed promoter reporter vectors, which we transfected into duck embryonic fibroblasts or chicken DF-1 cells and tested in dual luciferase assays. We showed that activation of the Mitochondrial Antiviral Signalling (MAVS) pathway using the constitutively active N-terminal region of RIG-I or polyinosinic-polycytidylic acid (poly I:C) led to stimulation of duck RIG-I promoter activity. Using deletion constructs we showed the core promoter lies in the proximal 250 basepairs, and we identified essential cis -regulatory elements, a GC-box and an interferon-sensitive response element (ISRE), responsible for basal and inducible expression, respectively. Using mCherry-tagged interferon regulatory factors (IRFs) cloned from chickens and ducks, we show overexpression of chIRF7 induced the duck RIG-I promoter, and this required the ISRE site. Finally, we also demonstrated that overexpressed chIRF7 translocated to the nucleus, which was augmented by MAVS activation using RIG-I 2CARD. Our findings demonstrate that RIG-I expression is induced by chIRF7, in a positive regulatory loop. These studies show that the duck RIG-I promoter is appropriately regulated in chicken cells, necessary for the potential generation of transgenic chickens expressing RIG-I.